Toxicological evaluation of Telfaria occidentalis and Talinum triangulare grown in freshly recovered petroleum-polluted soil - OLUA, VICTOR; NWAICHI, EUCHARIA OLUCHI; WEGWU, MATTHEW O. (European Journal of Applied Sciences, 2021)
Toxicity effect of Telfaria occidentalis and Talinum triangulare harvested from oil-polluted soil remediated using agro-waste formulations, on haematological indices of Wistar rats, was evaluated. Thirty-five rats grouped into seven of five rats each was used for this study. Group I received feed and water only, groups II & III received 1000mgkg-1 of Telfaria occidentalis and Talinum triangulare from unpolluted soil respectively, groups V & VI received 1000mgkg-1 of Telfaria occidentalis and Talinum triangulare from polluted but amended soil respectively, while groups IV & VII received 500mgkg-1 each of Telfaria occidentalis and Talinum triangulare from unpolluted and polluted but amended soil respectively. The results ranged as follows; PCV (47.30±1.21 to 54.06±0.78), Hb (15.19±0.27 to 17.20±0.20), RBC (4.79±0.07 to 5.67±0.07), WBC (3.37±0.16 to 3.84±0.09), and Platelet count (157.50±0.07 to 193.17±0.20). Obtained results showed that PCV, Hb and RBC counts of wistar rats treated combined leaf extract of Telfaria occidentalis and Talinum triangulare harvested from the amended soil were significantly increased (@p≤0.05) compared with the control group. This however suggests that the aqueous extract of T. occidentalis and T. triangulare harvested from the crude oil impacted farm remediated using selected agro waste formulation had no probable acute toxicity effects on the haematological parameters of Wistar albino rats as obtained values were within the reference ranges. Levels of haematological parameters obtained indicates that the plant extracts still maintained their blood boosting potentials with improved ability in enhancing erythropoiesis.